2011
DOI: 10.1068/ic871
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Olfactory and Somatosensory Perception: Do Odors in Close Categories have Similar Effects?

Abstract: In our previous experiments, it was shown that odors (rose, sandalwood) might influence the haptic perception (stiffness, roughness). In particular, subjects felt a smooth surface even smoother with rose odor and a stiff surface even harder with sandalwood odor. This study investigated whether the effects of odors could be explained by their categories that are derived from the verbal descriptions of odors. We used jasmine that is categorized as "flower", which includes rose, and peppermint that is categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results revealed that pleasant smell modulates roughness—that is, fabric swatches were judged as feeling softer in the presence of a pleasant odor (lemon in Experiment 1, lavender in Experiment 2) than in the presence of an unpleasant animal-like odour. That said, Nishino et al ( 2011 ), have reported inconsistent findings on the influence of odors, i.e., rose, sandalwood, on haptic perception (i.e., of stiffness and roughness).…”
Section: Crossmodal Interactions In Roughness Perceptionmentioning
confidence: 99%
“…The results revealed that pleasant smell modulates roughness—that is, fabric swatches were judged as feeling softer in the presence of a pleasant odor (lemon in Experiment 1, lavender in Experiment 2) than in the presence of an unpleasant animal-like odour. That said, Nishino et al ( 2011 ), have reported inconsistent findings on the influence of odors, i.e., rose, sandalwood, on haptic perception (i.e., of stiffness and roughness).…”
Section: Crossmodal Interactions In Roughness Perceptionmentioning
confidence: 99%